Metabolic evaluation of brain tumor using magnetic resonance spectroscopy. (2021) - Bibi, Sabah; Javid, Muhammad Arshad; Muhammad, Bilal; Sanauulah,; Habiba, Ume; Rashid, Quratulain; Amin, Niama; Khan, M. Umar; Aziz, Sumair
Abstract: The objective of this report is to assess lobe based metabolic evaluation of brain tumor in the masses of Pakistan using magnetic resonance spectroscopy. Forty four patients of brain tumor were scanned at MRI unit 1.5 Tesla in Bahawal Victoria Hospital Bahawalpur. H 1 MRS imaging was analyzed in different brain regions using IQ Viewer software. Brain tumor patients were scanned at short TE = 1.36 TR = 4.96 ms using STEAM technique. Data analysis was performed in software OrgionPro.8. The p-value (p ≤ 0.05) was deemed to see the results significantly. Out of forty four patients, 30 were graded low grade tumor with mean age with S.d (Male = 37.33 ± 19.18, Female = 45.53 ± 18.95) and 14 patients were noted high grade tumor with mean age (Male = 44 ± 14.67, Female = 34.25 ± 13.07). One way ANOVA test was applied to assess the difference among three metabolites ratio (Cho/NAA), (Cho/Cr) and (NAA/Cr) in high grade and low grade tumor patients. The ratio of metabolites (Cho/Cr), (NAA/Cr) and (Cho/NAA) remained insignificant with p-value male (p = 0.9) and female (p = 0.3) in low grade tumor. In high grade brain tumor, the ratio of (Cho/Cr), (NAA/Cr) and (Cho/NAA) also found insignificant with p-value male (p = 0.2) and female (p = 0.09). However, lobe based ratio of three metabolite showed no significant difference (p > 0.05) in low grade tumor and in high grade tumor. In addition, the most occurrence region in MRS images was found left and right parietal lobe with low and high grade tumor. This study concludes that decline of N-acetyl-aspartate (NAA) and elevation of choline metabolite induce the neuronal loss in brain tumor. The most occurrence region of brain tumor was appeared in parietal lobe and little injury was seen in occipital lobe in low and high grade tumor that determined the decline of sensory, ambulatory process and vision function in the masses of Pakistan.